Association between BDNF rs6265 and Obesity in the Boston Puerto Rican Health Study. (27th December 2012) - Ma, Xian-Yong; Qiu, Wei Qiao; Smith, Caren E.; Parnell, Laurence D.; Jiang, Zong-Yong; Ordovas, Jose M.; Tucker, Katherine L.; Lai, Chao-Qiang
Abstract : Brain-derived neurotrophic factor (BDNF) has been associated with regulation of body weight and appetite. The goal of this study was to examine the interactions of a functional variant (rs6265) in the BDNF gene with dietary intake for obesity traits in the Boston Puerto Rican Health Study. BDNF rs6265 was genotyped in 1147 Puerto Rican adults and examined for association with obesity-related traits. Men (n = 242 ) with the GG genotype had higher BMI (P = 0.009 ), waist circumference (P = 0.002 ), hip (P = 0.002 ), and weight (P = 0.03 ) than GA or AA carriers (n = 94 ). They had twice the risk of being overweight (BMI ≥ 25 ) relative to GA or AA carriers (OR = 2.08, CI = 1.02–4.23, and P = 0.043 ). Interactions between rs6265 and polyunsaturated fatty acids (PUFA) intake were associated with BMI, hip, and weight, and n-3 : n-6 PUFA ratio with waist circumference in men. In contrast, women (n = 595 ) with the GG genotype had significantly lower BMI (P = 0.009 ), hip (P = 0.029 ), and weight (P = 0.027 ) than GA or AA carriers (n = 216 ). Women with the GG genotype were 50% less likely to be overweight compared to GA or AA carriers (OR = 0.05, CI = 0.27–0.91, and P = 0.024 ). In summary, BDNF rs6265 is differentially associated with obesity risk by sex and interacts with PUFA intake influencing obesity traits in Boston Puerto Rican men.